Nutrition Education for Postpartum Women - Grace Falciglia; Julia Piazza; Erika Ritcher; Christina Reinerman; Seung Yeon Lee (SAGE Publishing, 2014)
This pilot study examined the effectiveness of a 4-month clinic-based dietary intervention emphasizing the intake of deep yellow and dark green vegetables versus usual care on improving diet quality in postpartum women. The intervention group (n = 31) received 1 face-to-face nutrition education session with a registered dietitian, 2 follow-up phone calls, and 3 pamphlets distributed by mail. The usual care group (n = 25) received handouts with guidelines on healthy eating. Dietary outcomes were assessed from 3-day food recalls and evaluated using paired and independent t tests. Intervention women exhibited a significant increase in total vegetable intake ( P < .001) and in dark green and deep yellow vegetables ( P < .001). In comparison, the control group increased the intake of total vegetables ( P < .001), but did not increase the consumption of dark green and deep yellow vegetables. When comparing the change in intake between study groups for both types of vegetables, the difference was not significant. Furthermore, 61% of the intervention women met the goals for total vegetable intake compared with 12% for the usual care group ( P < .001). The intervention group also had a greater percentage of women (25.8%) that met the goal for deep yellow and dark green vegetable intake when compared with the usual care group (8%; P < .08). These results suggest that postpartum women are receptive to nutrition education and that nutrition education can influence vegetable intake.